Diffusion-Weighted Magnetic Resonance Imaging Characterization of White Matter Injury Produced by Axon-Sparing Demyelination and Severe Contusion Spinal Cord Injury in Rats - Talbott, Jason F. (J Neurotrauma, 2016)
Alterations in magnetic resonance imaging (MRI)–derived measurements of water diffusion parallel (D∥) and perpendicular (D⊥) to white matter tracts have been specifically attributed to pathology of axons and myelin, respectively. We test the hypothesis that directional diffusion measurements can distinguish between axon-sparing chemical demyelination and severe contusion spinal cord white matter injury. Adult rats received either unilateral ethidium bromide (EB) microinjections (chemical demyelination) into the lateral funiculus of the spinal cord at C5 or were subjected to unilateral severe contusion spinal cord injury (SCI). Diffusion MRI metrics in the lateral funiculus were analyzed at early and late time-points following injury and correlated with histology. Early EB-demyelination resulted in a significant elevation in D⊥ and significant reduction in D∥ at the injury epicenter, with histological evidence of uniform axon preservation. Alterations in D⊥ and D∥ at the epicenter of early EB-demyelination were not significantly different from those observed with severe contusion at the epicenter, where histology demonstrated severe combined axonal and myelin injury. Diffusion abnormalities away from the injury epicenter were seen with contusion injury, but not with EB-demyelination. Chronic EB lesions underwent endogenous remyelination with normalization of diffusion metrics, whereas chronic contusion resulted in persistently altered diffusivities. In the early setting, directional diffusion measurements at the injury epicenter associated with chemical demyelination are indistinguishable from those seen with severe contusive SCI, despite dramatic pathologic differences between injury models. Caution is advised in interpretation of diffusion metrics with respect to specific white matter structural alterations. Diffusion analysis should not be limited to the epicenter of focal spinal lesions as alterations marginal to the epicenter are useful for assessing the nature of focal white matter injury.